Astragaloside IV attenuates hypoxia/reoxygenation injury-induced apoptosis of type II alveolar epithelial cells through miR-21-5p. Issue 1 (1st January 2021) - Li, Hang; Yao, Chang; Shi, Kaihu; Zhao, Yang; Du, Jin; Hu, Dinghui; Liu, Zuntao
ABSTRACT: We aimed to explore the role of miR-21-5p in the inhibitory effects of astragaloside IV (As-IV) on hypoxia/reoxygenation injury-induced apoptosis of type II alveolar epithelial cells. Rat type II alveolar epithelial cells RLE-6TN were cultured in vitro and randomly divided into control (C), hypoxia/reoxygenation injury (H/R), As-IV and miR-21-5p-siRNA + As-IV groups (n = 6). H/R model was established by 24 h of hypoxia and 4 h of reoxygenation. As-IV group was given 1 nmol/L As-IV and incubated for 1 h before modeling. MiR-21-5p-siRNA + As-IV group was transfected with 50 nmol/L miR-21-5p-siRNA. After 48 h, they were incubated with 1 nmol/L As-IV for 1 h before modeling. Cell viability was detected by cell counting kit-8 assay, and apoptosis rate was detected by flow cytometry. The expression levels of TLR4 and NF-κB were measured by immunofluorescence assay. The targeting relationship between miR-21-5p and TLR4 was determined by luciferase assay. Compared with H/R group, the cell viability, miR-21-5p, bax and cleaved caspase-3 expressions of As-IV group increased, apoptosis rate and Bcl-2 expression decreased, and TLR4 and NF-κB expressions were down-regulated (P < 0.05). Compared with As-IV group, the cell viability, miR-21-5p, bax and cleaved caspase-3 expressions of miR-21-5p-siRNA + As-IV group decreased, apoptosis rate and Bcl-2 expression increased, and the expressions of TLR4 and NF-κB were up-regulated (P < 0.05). As-IV up-regulates miR-21-5p expression, inhibits the TLR4/NF-κB signaling pathway and suppresses the apoptosis of type II alveolar epithelial cells during hypoxia/reoxygenation injury.